The ethics of smoking policies - Nixon, Judy C. (Journal of business ethics, 1989)
Smoking has long been declared a health hazard. In 1964, the U.S. Surgeon General revealed that smoking was related to lung cancer. Subsequent reports linked smoking to numerous other health problems. Recent statements by the Surgeon General indicated smokers do have the right to decide to continue or quit; however, their choice to continue cannot interfere with the nonsmoker's right to breathe smoke-free air., The full impact of adverse health consequences of involuntary smoking may not be recognized yet. Smoke is now known to affect everyone who breathes it. Even when one doesn't smoke, the nonsmoker is susceptible to the ill effects because of inhaling smoke., Are smoking policies justified? Companies are discovering that smoking has a negative economic and ethical impact on business. Smoking has been linked to increased health care costs, reduced productivity, increased absenteeism, and lowered morale., Has the number of smokers decreased? About 1.3 million smokers quit annually, while about one million young people begin annually. Businesses can help educate young people of health hazards of smoking., What are the effects of legal and ethical success of smoking policies? Results of a survey of U.S. corporations in 1987 indicated that 54 percent (increased from 36 percent in 1986) had smoking policies. A Federal Appeals Court judge ruled recently that smoking is not protected by the constitutional right to privacy.